Assessment of the influence of stress and anxiety on temporomandibular disorders (Research, Society and Development, 2021)
Objective: To analyze the influence of stress and anxiety on the severity degrees of temporomandibular disorders (TMD). Methodology: this was a descriptive study with a quantitative approach, carried out through digital platforms from April to June 2021. Individuals with temporomandibular disorder were included in the study. And those diagnosed with fibromyalgia, central or peripheral neurological disorders and depressive disorder were excluded. Previously, the Google Forms® link was shared for individuals complaining of a clinical TMD condition, followed by the filling out of the form by the participants, which lasted between 10 and 15 minutes. The form consists of 4 sections: Identification, Fonseca Anamnestic Index, State-Trait Anxiety Inventory (STAI) and Perceived Stress Scale (PSS-14). Results: 54 individuals participated in the study, being 88.9% female. The Fonseca classification showed a prevalence of mild severity (51.9%). Regarding the IDATE-E data, 32 participants had “low level of anxiety” (59.3%) and in the IDATE-T, 31 participants had “medium level of anxiety” (57.4%), with the lowest score of 5 for “high level of anxiety” (9.3%). On the PSS-14, scores ranging from 12 to 49 were found. The mean score was 29.06 (±8.5), and 50 participants had an “average level of perception” of stress (92.6%). Conclusion: There was a significant correlation between trait anxiety and TMD (p < 0.05).